Technological Advances in Winery Wastewater Treatment: A Comprehensive Review - Vlotman, David; Key, David; Bladergroen, Bernard. J. (South African Journal of Enology and Viticulture, 2022)
The commercial production of wine is directly linked to the use of large amounts of fresh water coupled with the generation of copious amounts of wastewater containing significant amounts of organic and inorganic substances. The impact of this waste stream on the environment has required the wine industry to implement certain protocols in wastewater management to comply with respective effluent discharge regulations as set out by local authorities. Reduced accessibility to good quality water resources in recent years has forced wineries to consider more efficient wastewater management strategies to improve water recovery and re-use, thereby promoting more sustainable wine production and minimizing the impact on stressed water resources. This review presents a comprehensive overview of established and emerging, physicochemical, biological, advanced oxidation and hybrid wastewater treatment technologies specifically applicable to the wine producing industry. Herein, winery wastewater composition and treatment techniques, environmental implications, knowledge gaps, technological operational challenges, alternative disposal and recycling options of treated winery wastewater are critically evaluated.